(untitled) (Journal of the College of Basic Education, 2022)
The present study was performed on 80 female subjects between (30-60) years, who attended the Specialized Center for Endocrinology and Diabetes during the period from April to July; 2011.The subjects were divided into 3 groups : controls , non diabetic autoimmune thyroid patients , and non diabetic autoimmune thyroid patient with renal diseases as complication . The results showed a significant increase in serum T3,T4 levels in hyperthyroidism patients, and significant decrease in serum T3,T4 levels in hypothyroidism patients ,while a significant difference in serum TSH levels in hyperthyroidism and hypothyroidism patients when compared to control group . The results show also a significant increase in serum antibodies to thyroid peroxidase(anti-TPO) level in both hyperthyroid and hypothyroid patient’s when compared to control group. In addition to, there was a significant increase in serum beta-2-microglobulin (β2M) level in thyroid patients and renal thyroid patients compared to control group, while there was no significant increase in serum β2M level in renal thyroid compared to thyroid patient’s. In conclusion, β2M can be used as a biomarker in autoimmune thyroid and renal autoimmune thyroid patient’s. In addition to the β2M level in renal thyroid diseases was higher than that in thyroid diseases. Key words: Autoimmune thyroid disease, β2M , renal diseases , anti-TPO . Autoimmune thyroid disease (AITD) is a common organ specific autoimmune disorder affecting mostly the middle aged women (30-50 years old). Thyroid autoimmunity can cause several forms of thyroiditis ranging from hypothyroidism ( Hashimotos thyroiditis) to hyperthyroidism (Graves Diseases). Both these disorders share many immunologic features and the diseases may progress from one state to other as the autoimmune process changes.Genetic , environmental and endogenous factors are responsible for initiation of thyroid autoimmunity(1). . Autoimmune thyroid diseases arise when the body attacks its own thyroid gland. When the immune system develops antibodies to thyroid tissue, it treats the thyroid gland as an invader of the body. This causes inflammation of the thyroid gland, which can destroy thyroid tissue over time. The thyroid is responsible for creating two hormones, triiodothyronine and thyroxine. Low levels of these hormones can lead to the symptoms of autoimmune thyroid disease ( 2).